Стихи Геннадия Айги – бессмыслица или лирика? (Gennadi Aigi’s Verse — Nonsense or Lyrics?) - Erik Egeberg (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2000)
In this paper some characteristic features of Aigi's poetry which are usually regarded as unconventional and troublesome, e.g. the absence of verbs, capital letters and punctuation marks, are briefly discussed with the aim of defining his method of creating meaning. The paper concludes with the assertion that Aigi is giving the reader a new role as co-creator of the poem.